KOMUNIKASI KEBIJAKAN PADA PENGADAAN TANAH UNTUK PEMBANGUNAN INFRASTRUKTUR JALAN TOL PEMATANGSIANTAR – PARAPAT - Lia Nur Syahputri Siregar; Victor Lumbanraja (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the implementation of public policy communication in the land acquisition process for the construction of the Pematangsiantar–Parapat toll road, particularly within the Pematangsiantar City area. The main focus of this research is to examine the effectiveness of policy communication based on four key indicators proposed by Charles O. Jones: message clarity, communication channels, policy implementer structure, and public response. In addition, the study identifies supporting and inhibiting factors in policy communication implementation, as well as the forms of community response and participation in the land acquisition process. This research employs a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews with key informants, documentation, and field observation. The findings reveal that the government’s policy communication has not been fully effective. Although formal communication channels such as meetings and public outreach have been utilized, challenges remain in terms of message clarity, limited community involvement in deliberations, and distrust in the compensation determination process. Supporting factors include regulatory backing and the presence of a land acquisition team, while major inhibiting factors involve information asymmetry and public resistance due to perceived exclusion. The study concludes that the success of land acquisition is highly dependent on the effectiveness of public policy communication conducted by the government. There is a need for improved communication strategies that are more participatory, transparent, and